Explanation of core ion cyclotron emission from beam-ion heated plasmas in ASDEX Upgrade by the magnetoacoustic cyclotron instability. (21st December 2020) - Liu, Lunan; Ochoukov, R.; McClements, K.G.; Dendy, R.O.; Bobkov, V.; Weiland, M.; Bilato, R.; Faugel, H.; Moseev, D.; Salewski, M.; Zhang, Wei; Zhang, Xinjun; et al.
Abstract: Bursts of ion cyclotron emission (ICE), with spectral peaks corresponding to the hydrogen cyclotron harmonic frequencies in the plasma core are detected from helium plasmas heated by sub-Alfvénic beam-injected hydrogen ions in the ASDEX Upgrade tokamak. Based on the fast ion distribution function obtained from TRANSP/NUBEAM code, together with a linear analytical theory of the magnetoacoustic cyclotron instability (MCI), the growth rates of MCI could be calculated. In our theoretical and experimental studies, we found that the excitation mechanism of core ICE driven by sub-Alfvénic beam ions in ASDEX Upgrade is MCI as the time evolution of MCI growth rates is broadly consistent with measured ICE amplitudes. The MCI growth rate is very sensitive to the energy and velocity distribution of beam-injected ions and is suppressed by the slowing down of the dominant beam-injected ion velocity and the spreading of the fast ion distribution profile. This may help to account for the experimental observation that ICE signals disappear within ∼3 ms after the NBI turn-off time, much faster than the slowing down times of the beam ions.